Underpricing & performance of seasoned equity offerings : the role of corporate governance. - Luo, Sean Melvyn Jia-Da. (2008)
Using a sample of 1402 public companies in the United States, our study provides empirical evidence on the impact of five corporate governance mechanisms, namely (i) CEO duality, (ii) Board independence, (iii) Board size, (iv) Managerial ownership and (v) Institutional ownership, on SEO underpricing and SEO firm performance.